Assessment of physico- chemical properties and microbial community during composting of municipal solid waste (Viz. KItchen waste) at Jhansi City, U.P. (India) - Pathak, A K; Singh, M M; Kumara, V; Arya, S; Trivedi, A K (Recent Research in Science and Technology, 2012)
Rapid industrialization and population explosion in India has led to the migration of people from villages to cities, which generate thousands of tons of Municipal Solid Waste (viz. Kitchen waste) MSW (Viz. KW) daily. Jhansi City is well known district of Bundelkhand region of Uttar Pradesh (India) with a geographical area of 502.75 thousand hectare. The district is situated in the South West corner of the region at 24º11’ - 25º57’ N latitude and 78º10’ - 79º23’ E longitudes. Population of Jhansi city is near about 4,79, 612. A detail study was conducted in four consecutive years to assess the potential and possibilities of MSW (Viz. KW) composting generated from Jhansi city, Uttar Pradesh. In the present study, we studied physico-chemical parameters and succession of microbial populations during composting process of MSW (Viz. KW) and found that the pH ranged between 7.1-7.9, Temperature 14-65.2°C, Organic Carbon 20-26 %, moisture content 22-66.7 %, nutrients N – 1.16 %, P – 0.04 %, K – 0.34%, Na – 2.89 % and microbial colonies like Bacteria, fungi, and Actinomycetes were also present in large numbers.Temperature plays an important role in the growth of microbial colonies during composting of Municipal Solid waste (Viz. Kitchen Waste).